2017
DOI: 10.1007/s00345-017-2130-5
|View full text |Cite
|
Sign up to set email alerts
|

PSA kinetics following primary focal cryotherapy (hemiablation) in organ-confined prostate cancer patients

Abstract: A significant drop in post-PFC PSA may indicate elimination of the index lesion. Patients who are likely to recur biochemically have a significantly higher PSAV compared to those who do not recur. Nadir PSA of less than 2 ng/ml may be considered the new normal PSA in focal cryotherapy (hemiablation) follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…Prostate specific antigen measurements were performed at short intervals (every 1-3 months) post-operatively. Biochemical recurrence (BCR) was determined using Phoenix criterion (PSA nadir + 2 ng/ml) [13,14]. If the PSA level increased to the pre-treatment level, we recommended a 5-mm transperineal template mapping biopsy (TTMB).…”
Section: Patient Follow-up (Psa Mri and Toxicity)mentioning
confidence: 99%
“…Prostate specific antigen measurements were performed at short intervals (every 1-3 months) post-operatively. Biochemical recurrence (BCR) was determined using Phoenix criterion (PSA nadir + 2 ng/ml) [13,14]. If the PSA level increased to the pre-treatment level, we recommended a 5-mm transperineal template mapping biopsy (TTMB).…”
Section: Patient Follow-up (Psa Mri and Toxicity)mentioning
confidence: 99%
“…The lack of clarity arises due to the intrinsically personalized nature of focal treatment, where a small treatment in a large prostate will have less of an impact on PSA than a hemi-ablation in a small gland. However, PSA kinetics and particularly PSA nadir have been proposed as potential post-operative tools to predict FT failure [9,10], and to tailor the follow up MRI schedule for men. In the current study we sought to determine the relationship of the percentage of PSA reduction (%PSA reduction) after FT using high-intensity focused ultrasound (HIFU) in predicting the risk of for any additional treatment and radical treatment.…”
mentioning
confidence: 99%
“…Gleason score, clinical stage, PSA and prostate volume). Even though PSA nadir had been proposed as useful post-FT tool [9,10], its value is highly influenced by several factors such as pre-operative PSA, prostate volume and the prostatic tissue ablated during treatment. The use of %PSA reduction allows to overcome all these confounders.…”
mentioning
confidence: 99%
“…The search protocol yielded 13 studies that were identified for inclusion after thorough assessment (Figure 1) (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). Eight studies were single center series, while three were multicenter cohorts and two were derived from the Cryo On-Line Data (COLD) multi-center registry.…”
Section: Resultsmentioning
confidence: 99%
“…Eleven (84.6%) studies specifically analyzed oncologic outcomes, which are presented in 22.8 months (15), two studies quoted 3-year BCRFS from 56-62.5% (13,16), and two articles described 5-year rates from 62-70% (14,21). Nine (69.2%) studies reported follow-up biopsy data, with 23.8-96.6% of patients undergoing post-cryoablation biopsy.…”
Section: Oncologic Outcomesmentioning
confidence: 99%